2020
DOI: 10.1186/s12866-020-01928-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction and screening of a glycosylphosphatidylinositol protein deletion library in Pichia pastoris

Abstract: Background: Glycosylphosphatidylinositol (GPI)-anchored glycoproteins have diverse intrinsic functions in yeasts, and they also have different uses in vitro. In this study, the functions of potential GPI proteins in Pichia pastoris were explored by gene knockout approaches. Results: Through an extensive knockout of GPI proteins in P. pastoris, a single-gene deletion library was constructed for 45 predicted GPI proteins. The knockout of proteins may lead to the activation of a cellular response named the 'compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Activity assay of the displayed enzymes showed that the Cb FDH-Pir1 and YADH-Agα1 constructs exhibited functional enzymes on the cell surface (Figure S16), while the constructs with Pc FaldDH failed to show activity after displaying it on the cell surface. Other six FaldDHs from different organisms were also displayed with three other GPI anchor motifs (Table S1), and these constructs failed to generate a viable strain with the activity of FaldDH. Therefore, free Pc FaldDH was used with displayed Cb FDH and YADH to construct a multienzyme assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Activity assay of the displayed enzymes showed that the Cb FDH-Pir1 and YADH-Agα1 constructs exhibited functional enzymes on the cell surface (Figure S16), while the constructs with Pc FaldDH failed to show activity after displaying it on the cell surface. Other six FaldDHs from different organisms were also displayed with three other GPI anchor motifs (Table S1), and these constructs failed to generate a viable strain with the activity of FaldDH. Therefore, free Pc FaldDH was used with displayed Cb FDH and YADH to construct a multienzyme assembly.…”
Section: Resultsmentioning
confidence: 99%